Green accounting in maintaining the economic stability of MSMEs amid the impact of the MBG program towards a golden Indonesia - Selomitha Salsabila; Cintia Dewi Partika Sari; Syabila Nova Azzahra (Institute for Advanced Social, Science, and Sustainable Future, 2026)
Background: Transformation towards a green economy is one of the main directions of national development in realizing the vision of Golden Indonesia 2045, with micro, small, and medium enterprises (MSMEs) as key actors in the economy. On the other hand, the implementation of the Free Nutritious Meal Program (MBG) has economic implications for MSMEs, especially changes in demand patterns and local business dynamics. This research aims to analyze the role of green accounting as a strategic instrument in maintaining the stability and sustainability of MSMEs in the midst of the impact of MBG policies. Methods: This study employs a literature review method using structured thematic analysis of secondary sources from academic databases and official publications, systematically categorizing and synthesizing studies on green accounting, MSME sustainability, and related policies to identify patterns, theoretical linkages, and research gaps, thereby constructing a conceptual framework connecting environmental accounting practices with economic resilience within Indonesia’s policy context. Findings: The findings indicate that green accounting strengthens MSMEs’ environmental responsibility, operational efficiency, and economic resilience amid the implementation of the Free Nutritious Meal (MBG) program, enabling better cost management, sustainability reporting, and competitiveness; however, its adoption remains constrained by limited financial and human resources, highlighting the need for institutional support, digital tools, and policy incentives to optimize its contribution to sustainable national development and the SDGs toward Indonesia Emas 2045. Conclusion: These findings confirm that green accounting not only functions as a recording tool for environmental accounting, but also as an adaptive mechanism that bridges the government's social policies with the economic resilience of MSMEs. Novelty/Originality of this article: This research contributes to the development of sustainable accounting studies by placing green accounting as a strategic foundation for strengthening MSMEs that are inclusive and in line with the sustainable development agenda towards a Golden Indonesia 2045.